Adipocyte-derived players in hematologic tumors: useful novel targets?. (January 2015) - Jöhrer, Karin; Ploner, Christian; Thangavadivel, Shanmugapriya; Wuggenig, Philipp; Greil, Richard
<x xml:space="preserve">Abstract</x> Introduction: Adipocytes and their products play essential roles in tumor establishment and progression. As the main cellular component of the bone marrow, adipocytes may contribute to the development of hematologic tumors. Areas covered: This review summarizes experimental data on adipocytes and their interaction with various cancer cells. Special focus is set on the interactions of bone marrow adipocytes and normal and transformed cells of the hematopoietic system such as myeloma and leukemia cells. Current in vitro and in vivo data are summarized and the potential of novel therapeutic targets is critically discussed. Expert opinion: Targeting lipid metabolism of cancer cells and adipocytes in combination with standard therapeutics might open novel therapeutic avenues in these cancer entities. Adipocyte-derived products such as free fatty acids and specific adipokines such as adiponectin may be vital anti-cancer targets in hematologic malignancies. However, available data on lipid metabolism is currently mostly referring to peripheral fat cell/cancer cell interactions and results need to be evaluated specifically for the bone marrow niche.